Multi-kinase inhibitors and cisplatin for head and neck cancer treatment in vitro - Brands, Roman C. (Oncol Lett, 2019)
Multidrug resistance (MDR) remains one of the major causes of suboptimal outcome following therapy in head and neck squamous cell carcinoma (HNSCC). ATP-binding cassette (ABC) transporters are overexpressed in HNSCC, which contributes to the limited effect of chemotherapeutic treatment. In addition to their named function, tyrosine kinase inhibitors (TKIs) have been revealed to impact on ABC transporter activity and expression. Therefore, the present study aimed to investigate the effects of combination therapy using different TKIs combined with cisplatin. Reverse transcription-quantitative PCR was used to characterize ABC transporter and receptor expression in 5 HNSCC cell lines treated with 3 different TKIs (pazopanib, dovitinib, nintedanib) and cisplatin. Treatment efficacy was analyzed using a crystal violet staining assay. Analysis of ABC transporter (ABCB1, ABCC1 and ABCG2) genetic alterations was performed using The Cancer Genome Atlas. Statistical analysis was conducted to evaluate the effects of mono- and combination treatment. With the exception of ABCB1, all of the investigated ABC transporters were expressed in each cell line. The additive effects of TKI + cisplatin combination treatment were observed for pazopanib in three cell lines, nintedanib in four cell lines, and were not observed for dovitinib in any of the cell lines investigated. The combination of multi-kinase inhibitors and conventional chemotherapy in HNSCC may strengthen the use of current therapeutic strategies; nintedanib appears to be the most suitable TKI for combination therapy. Further efforts are required to classify TKI efficacy with regard to cisplatin resistance.